Education and everyday realities of the Third Reich: memoirs and theoretical reconstructions - Maria Kultaieva (Філософія освіти, 2018)
The everyday realities of educational practices of the Third Reich are reconstructed in the memoires of involved observers of these processes.  The most of them can be used as a factual supplement to theoretical reflections on totalitarian transformations in education as their subjective perceiving.  Despite of different origin and life attitudes all the authors of translated fragments are concentrated on those features of totalitarian educational innovations which show their completely incompatibility with the humanistic tradition in education. The everyday life of universities’ and school’s communities in the Third Reich was determined by the national-socialist ideology.